DU PONT SYSTEM ANALYSIS IN MEASURING COMPANY FINANCIAL PERFORMANCE (CASE STUDY OF BANK CENTRAL ASIA AND BANK RAKYAT INDONESIA PERIOD 2021-2023) - Rani Fitria ,; Putri Melani ,; Wiwik Apriani ,; Dwi Saraswati , (WANARGI : Jurnal Manajemen Dan Akuntansi, 2025)
The two largest banks in Indonesia are Bank Central Asia (BCA) and Bank Rakyat Indonesia (BRI). The financial performance of both is a key indicator to assess the health and operational effectiveness of a bank. This study uses the DuPont Analysis approach to examine the financial performance of BCA and BRI. Secondary data from the annual financial statements of both banks for 2021–2023 are used in this investigation. In 2021–2023, BCA's average net profit margin (NPM) was 61%, according to the study's findings, while BRI's NPM was 38%, increasing to 63% in 2023. When compared to the industry standard of 0.05-0.1, the TATO of both banks is in a reasonable range, with BRI showing a more productive performance. Meanwhile, the average return on equity (ROE) is 3%, higher than BRI's 2.5%. According to DuPont's analysis, BCA appears to be superior to BRI in terms of operational efficiency and profitability, as evidenced by its better NPM and ROE. For investors and bank management, among other stakeholders, these findings offer important insights into the dynamics of banks’ financial performance and the potential impact of various initiatives on their bottom lines.